ETR 300 Sport revolution centre / Mohd Azroff Yusup...(et al.) - Yusup, Mohd Azroff; Sabeki, Siti Nur Adilah; Yusuf, Siti Nurfariesha; Awang Omar, Dayang Nurfatin; Awang Basuandi, Dayangku Aisyah (2015)
We must have an efficient and comprehensive method of management in an administration of business. All partners must involve in this strategic management. The most important thing that we must take care is efficiency in management. To make sure our objective can be accomplished we have to put our effort in preparing this business proposal. Marketing, production and financial aspect must be considered which consist of a complete term of management that is planning, organizing, leading, and controlling. All this aspect really assists in achieving our goals. Administration must also set the company's vision and mission, which can be used by the organization as a guideline to earn profit. Other than that, administration also includes the allocation of resources to avoid wastage besides giving a better development based on the monetary value of every department. Another responsibility of administration is determining the process in achieving the organizational goals where this administration needs to ensure all of the department cooperate with each other. A part from that, the administration must able to provide better services for the employees. For example, welfare, allowances, SOCSO, EPF and other benefits to make employees feel secure working in our company. The roles played by the administration department really determine the effectiveness and efficiency of our organization to make sure our goals can be achieved.